Buffer Solution Reduces Acidic Toothpaste Abrasivity Measured in Standardized Tests - Zehnder, Matthias; Masoch, Luca; Gubler, Andrea; Mohn, Dirk; Attin, Thomas; Wegehaupt, Florian J. (Frontiers in Dental Medicine, 2020)
It has been speculated that the diluent used to test toothpaste abrasivity in standard tests may have an impact on their results, especially in the context of acidic toothpastes. This study tested whether an acidic toothpaste is indeed more abrasive than a neutral counterpart of otherwise identical composition, and whether this increased abrasivity is prevented by a buffered solution simulating saliva. Two experimental toothpastes of identical composition yet different pH (7.0 versus 5.0) were prepared using standard ingredients. Subsequently, they were tested in standard absolute dentin abrasion and relative dentin abrasivity (RDA) experiments. To prepare slurries for these tests, deionized water as recommended by the International Organization for Standardization (ISO 11609:2017) was used, or a buffer solution containing bicarbonate and phosphate. The pH in these slurries was assessed and compared to the pH obtained in oral slurries of healthy individuals. Results showed that a significant (one-way ANOVA, p < 0.05) increase in mean absolute dentin abrasion and RDA values by 35% and 14%, respectively, was obtained when water was used as the diluent in conjunction with the acidic toothpaste as compared to the buffer solution. This was not the case with the neutral toothpaste. This result was explained by the finding that the buffer solution neutralized the pH in experimental slurries of the acidic toothpaste, while deionized water was unable to elevate the pH of the acidic toothpaste. That toothpaste was also neutralized in oral slurries. It was concluded that indeed the current ISO standard may result in a systematic overestimation of acidic toothpaste abrasivity.